2009
DOI: 10.1007/s12289-009-0505-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the thermal behavior of ultra high strength boron manganese steels within hot stamping

Abstract: The increasing demand for high strength steels regarding light weight construction design for the body in white is enforcing the automotive industry to onset more and more innovative forming technologies due to the reduced formability of such high strength steel grades. The hot stamping of boron manganese steels is hereby one of the main forming processes to be named. Besides the commonly used forming strategy where a homogeneous distribution of the material parameters is achieved, the partial press hardening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 3 publications
2
29
0
1
Order By: Relevance
“…Turetta [5] plotted 22MnB5 steel cooling curves and demonstrated that the higher the contact pressure the higher the cooling rate is. Similar results were reported by several authors [11][12][13][14][15].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Turetta [5] plotted 22MnB5 steel cooling curves and demonstrated that the higher the contact pressure the higher the cooling rate is. Similar results were reported by several authors [11][12][13][14][15].…”
Section: Introductionsupporting
confidence: 92%
“…Turetta [5] plotted 22MnB5 steel cooling curves and demonstrated that the higher the contact pressure the higher the cooling rate is. Similar results were reported by several authors [11][12][13][14][15].It has been observed that most of the experimental apparatus and industrial processes operate with closure pressures higher than 10MPa. In this study, a die quenching experimental method, using low closing pressures and an aluminum flat die, was developed in order to simulate characteristic events of the hot stamping process.…”
supporting
confidence: 90%
“…Hot stamping can be used to produce the components with distributed microstructure and mechanical properties by using the slow cooling rate for the special region in hot stamping [12]. Local reductions of cooling rate can be achieved by using the thin air gap between the tools and the blank [13], controlling the temperature of tools [14], or using the steel with the lower thermal conductivity in the tools [15].…”
Section: List Of Symbols Kmentioning
confidence: 99%
“…Subsequently, the formed components can be artificially aged to obtain maximum strength [6]. As the HFQ process is a non-isothermal process, and a high friction coefficient is typically observed at elevated temperatures [7], the thermal and tribological properties at the tool/work-piece interface significantly affect formability in the forming process [8][9].…”
Section: Introductionmentioning
confidence: 99%